The influence of leadership in creating creativity and developing performance - Hafez, Hassan Mohamed Hassan (Journal of Economic, Administrative and Legal Sciences, 2017)
The research dealt with the influence of leadership in creating creativity and developing performance. Case study (Saudi Company for Hotels and Tourism Areas). The research relied on the following hypotheses: Administrative leadership plays a key role in the development of the performance of the employees of Saudi Hotels and Tourism Areas. There is a positive relationship between the ownership of the administrative leaders of the Saudi Company for Hotels and Touristic Areas of the personality and characteristics of the administrative leader and the ownership of managers. A statistically significant relationship between the manager's practices (the leader) and the impact of these practices on the loyalty of employees and their desire to work. The descriptive descriptive method and the historical narrative were used in preparing the study. The researcher treated the data obtained from the field study statistically using the SPSS. The study reached many conclusions, the most important of which is to prove the validity of the above hypotheses. The research also reached many recommendations that can be of benefit to the decision makers in the private and public sectors, the most important of which is: increasing the interest in the humanitarian aspect in dealing between presidents and subordinates. Study the conditions of employees in the Saudi Company for Hotels and Tourist Areas and work to solve the problems facing them. Work on improving the environment of the administrative environment in Saudi Hotels and Tourist Areas.
Keywords: leadership; organizational variables; administrative environment; job performance; creative productivity